Estimation of urban heat islands in the city of Uruapan, Michoacan, Mexico - Manzanilla Quiñones, Ulises (Ecosistemas y Recursos Agropecuarios, 2023)
The objective of this research was to determine urban heat islands (UHI) through the use of meteorological data of maximum temperature and satellite images in Uruapan, Michoacan, Mexico. Using maximum temperature records from the Jicalán meteorological station (CFE) from the period 1963-1998 and Landsat 8 OLI satellite images from the period 2013-2021, the average instrumental and satellite maximum temperature during the canícula was calculated. The estimation of the UHI was performed by applying a value of +1°C above the historical average temperature value recorded by the Jicalán meteorological station (CFE), that is to say, areas above +1 °C of the average temperature value. The UHI identified were 23, covering an area of 146.8 ha. In conclusion, it can be said that 95.6% of the UHI are concentrated in the south-central part of Uruapan, with values ranging from 1 to 3.9 °C.